Perceptions of office rent determinants by real estate brokerage firms in Istanbul - Oven, VA; Pekdemir, D (Routledge Journals, Taylor & Francis Ltd, 2006)
Studies on the office rent prediction models have been on the rise for the last quarter of this century. The extent of variables used in the proposed models changes significantly, reflecting variations in locational and/or economical conditions of the region. The viewpoint of brokerage firms on the effectiveness of these academically defined variables is important. The benefit of obtaining these viewpoints is two-fold. Firstly, it will provide some evidence on whether or not the reported influences of these variables remain the same in different markets, in this case, in the Istanbul office market. Secondly, it may define how well practitioners' criteria fit academically defined variables during the decision-making process for a new office investment, especially in the Istanbul office market. The study derives the currently well established locational, building, econometric and contract variables from previously published research. Two different influence scales of these variables were constructed. The first scale was based on the result of a survey study administrated to 10 leading real estate brokerage firms in Istanbul and the second was based on the reported influences from previous publications. Comparing the influence scales, contradictory and parallel findings were determined, indicative conclusions, revealing the unique structure of Istanbul, were drawn. Among the 47 comparable office rent variables, the influence of 17 was found to agree well in both scales. Except econometric variables, most variables in Istanbul revealed different influences than globally determined influences.
Keywords: Market; Sector; Area